Study of Analgesic Effect of Magnesium Sulphate with Bupivacaine in Ultrasonogram Guided Transversus Abdominis Plane Block for Post-Operative Analgesia in Lower Uterine Cesarean Section (Community Based Medical Journal, 2022)
Background: Transversus abdominis plane (TAP) block has proven to be an effective component of postoperative pain management for different abdominal procedures particularly in Lower uterine cesarean section (LUCS) done under Sub arachnoid block. Magnesium sulphate (MgSO4) is a N-methyl-D-aspartate receptor antagonist has the potential to act as an adjuvant in TAP block. For this reason this study was planned to assess the role of Magnesium Sulphate as an adjuvant to bupivacaine in ultrasound-guided transverse abdominis plane (TAP) blocks for postoperative analgesia in patients undergoing LUCS after regression of block of Sub arachnoid block.Methods: This was a hospital based randomized controlled trial which was conducted in Dhaka Medical College Hospital (DMCH) at the department of Anaesthesia, Analgesia, Palliative & Intensive Care Medicine for 2 years of period. Formal ethical approval was taken from the Ethical Review Committee (ERC) of DMC. Patients having LUCS were approached for the study. A total of 60 patients of LUCS under Sub arachnoid block were selected in the study among them 30 patients received TAP block with bupivacaine 0.25% with saline, and the other 30 received bupivacaine 0.25% with 150 mg Magnesium Sulphate immediately following surgery. Primary outcome was focused on duration of analgesia, pain score, time of first need of rescue analgesic and total opioid consumption. Pre-block and immediately post block Visual analog pain scores (VAS) (0–10) were obtained. After pre-anesthetic checkup & discussion about study procedures written informed consent was taken from the patient. Separate case record form was used in each case. Data analysis was done by SPSS version 22.Observation and Results: Mean age of group B (GB) and group-BM (GBM) patients were 25.57± 2.76 & 25.9 ± 3.17SD (years). No significant difference demographic profile was observed (p>0.05). Mean duration of analgesia was significantly prolonged in Group BM compared to Group B (263.13 ± 34.39) min vs. 222.23 ± 30.58 min; P-value